HUBUNGAN FAKTOR LINGKUNGAN KIMIA, FISIKA TERHADAP DISTRIBUSI PLANKTON DI PERAIRAN BELITUNG TIMUR, BANGKA BELITUNG - Marojahan Simanjuntak (Universitas Gadjah Mada, 2009)
The purpose of this study was to know the distribution of nutrients and their effect to the distribution of phytoplankton in the eastern area of Belitung water. Sampling was done on October 2006. Water samples were collected from the surface and at depth 10 m among 10 stations. For chemical and physical properties, samples were collected from both of surface and at depth 10 m while for phytoplankton content, samples were collected from surface water. Samples were analyzed for phosphate, nitrate, nitrite, ammonia, silicate, pH, dissolved oxygen, temperature, salinity and concentration of plankton. The result showed that the concentration of phosphate, nitrate, nitrite and silicate were tended to decrease followed to the distance of station from the shore line. Dissolved oxygen and phytoplankton were tended to decrease as the depth. There was positive correlation between salinity and concentration of plankton. It led to conclusion that the water was still suitable for living biota.